First Case of Visceral Leishmaniasis Caused by Leishmania martiniquensis - Liautaud, Bernard (Am J Trop Med Hyg, 2015)
We report the first case of visceral leishmaniasis (VL) caused by Leishmania martiniquensis in the Caribbean, which until now, was known only to cause cutaneous leishmaniasis. The disease presented with fatigue, anemia, and hepatosplenomegaly in a 61-year-old man with human immunodeficiency virus (HIV) infection who was receiving antiretroviral therapy. Diagnosis was made by bone marrow biopsy. VL is life-threatening, and its emergence in the Caribbean is of concern.